STUDENTS’ PERCEPTION ON THE DESIGN OF ASYNCHRONOUS ONLINE DISCUSSION USING SCHOOLOGY IN ENGLISH LANGUAGE EDUCATION GANESHA UNIVERSITY OF EDUCATION - G.P.R, Dewi; L.D.S., Adnyani; K.S., Piscayanti (Universitas Pendidikan Ganesha, 2019)
This study was aimed at investigating students’ perception on the design of asynchronous online discussion using Schoology. This study was a case study research. The data in this study were collected quantitatively and qualitatively by using observation, questionnaire, and interview guide. The observation was conducted toward the design of asynchronous online discussion implemented by 2 lecturers in ICT and Poetry courses. The questionnaire was administered to one hundred students of English Language Education, Ganesha University of Education who were taught using Schoology in academic year 2017/2018. The interviews were done toward six students. The result of this study showed that 1) the design of the asynchronous online discussion in ICT and Poetry courses was different in terms of flexibility of time, flexibility of place, instruction or guidance, and topic, 2) the students had positive perception on the design of asynchronous online discussion.